2021
DOI: 10.1055/a-1486-7148
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Spontaneous Preterm Birth in At-risk Women Using Thrombospondin 1 from Cervicovaginal Fluid: A Prospective Observational Study

Abstract: Introduction Thrombospondin 1, desmoplakin and stratifin are putative biomarkers for the prediction of preterm birth. This study aimed to validate the predictive capability of these biomarkers in patients at risk of preterm birth. Materials and Methods We included 109 women with symptoms of threatened spontaneous preterm birth between weeks 20 0/7 and 31 6/7 of gestation. Inclusion criteria were uterine contractions, cervical length of less than 25 mm, or a personal history of spontaneous preterm bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Our robust marker selection process took into account the performance of individual markers, combinatorial effects with other markers, and stability. Many markers that were identified, such as A1BG 24 , ALB 34,44 , FN1 35,49 , GC 34,36,50 , TF 24,49 , TIMP1 36,39 , and THBS1 37,51 , align with previous findings, while novel markers, like LUM, AMBP, B2M, PRG2, ZG16B, and PSG1 were discovered. Function analysis revealed that proteins significantly upregulated in sPTB samples were associated with abnormal activation of the complement system, extracellular matrix remodeling, and serine protease inhibitor activity.…”
Section: Discussionsupporting
confidence: 85%
“…Our robust marker selection process took into account the performance of individual markers, combinatorial effects with other markers, and stability. Many markers that were identified, such as A1BG 24 , ALB 34,44 , FN1 35,49 , GC 34,36,50 , TF 24,49 , TIMP1 36,39 , and THBS1 37,51 , align with previous findings, while novel markers, like LUM, AMBP, B2M, PRG2, ZG16B, and PSG1 were discovered. Function analysis revealed that proteins significantly upregulated in sPTB samples were associated with abnormal activation of the complement system, extracellular matrix remodeling, and serine protease inhibitor activity.…”
Section: Discussionsupporting
confidence: 85%
“…The study was conducted as part of the “Analysis of diagnostic accuracy of predictive biomarkers in risk assessment of threatening preterm birth” (ADAPROB) study, parts of which have already been published [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Around 10.6% of all deliveries worldwide are premature 4 . The number of premature deliveries in Germany has remained almost the same in recent years; in 2008, it was 8.0% and in Austria it was 7.9% in 2016 5 .…”
Section: Introductionmentioning
confidence: 99%